Leaf traits and herbivory levels in a tropical gymnosperm, Zamia stevensonii (Zamiaceae)1. Issue 3 (1st March 2014) - Prado, Alberto; Sierra, Adriel; Windsor, Donald; Bede, Jacqueline C.
Abstract : Premise of the study: Slow‐growing understory cycads invest heavily in defenses to protect the few leaves they produce annually. The Neotropical cycad Zamia stevensonii has chemical and mechanical barriers against insect herbivores. Mechanical barriers, such as leaf toughness, can be established only after the leaf has expanded. Therefore, chemical defenses may be important during leaf expansion. How changes in leaf traits affect the feeding activity of cycad specialist insects is unknown. We investigated leaf defenses and incidence of specialist herbivores on Z. stevensonii during the first year after leaf flush. Methods: Herbivore incidence, leaf production, and leaf traits that might affect herbivory—including leaf age, lamina thickness, resistance‐to‐fracture, work‐to‐fracture, trichome density, and chlorophyll, water, and toxic azoxyglycoside (AZG) content—were measured throughout leaf development. Principal component analysis and generalized linear models identified characteristics that may explain herbivore incidence. Key results: Synchronized leaf development in Z. stevensonii is characterized by quick leaf expansion and delayed greening. Specialist herbivores feed on leaves between 10 and 100 d after flush and damage ∼37% of all leaflets produced. Young leaves are protected by AZGs, but these defenses rapidly decrease as leaves expand. Leaves older than 100 d are protected by toughness. Conclusions: Because AZG concentrations drop before leaves become sufficiently tough, there is a vulnerable period during which leaves are susceptible to herbivory by specialist insects. This slow‐growing gymnosperm invests heavily in constitutive defenses against highly specialized herbivores, underlining the convergence in defensive syndromes by major plant lineages.